Performance and environmental impacts of waste plastic-modified asphalt pavement: A comprehensive review - Wu, Xingchi; Jusli, Euniza; Anggraini, Wresni; Putra Jaya, Ramadhansyah; Zhang, Xinqiang (Elsevier Ltd., 2025)
Plastic waste has become a major global concern due to its adverse environmental and human health impacts. Incorporating waste plastic into asphalt pavements provides a sustainable solution that reduces pollution while enhancing pavement performance. This review synthesises recent advances (2021–2025) in plastic-modified bitumen and asphalt by integrating engineering performance, environmental risk, and life cycle assessment (LCA) perspectives. It develops a clear framework that links material performance with environmental emissions and overall sustainability, and highlights key research gaps related to materials utilisation, microplastic release, recyclability and LCA. Findings indicate that plastic modification improves rutting resistance, fatigue life, and moisture durability, and reduces emissions of harmful substances during production and service, which aligns with SDG 12, 13, and 14. In addition, the integration of waste plastics into asphalt enables cleaner material pathways by minimising the reliance on virgin polymers and mitigating emissions during production and application stages. However, challenges such as poor plastic-bitumen compatibility and limited low-temperature flexibility persist. The review further highlights the need for standardised datasets, region-specific LCAs, and long-term field monitoring to ensure reliable environmental assessments. Overall, this study provides an updated synthesis and research roadmap for materials scientists, pavement engineers, and policymakers to advance the sustainable design, evaluation, and large-scale implementation of waste plastic-modified asphalt pavements within a circular-economy framework.